Problematic Internet Use digunakan Ketika Kesepian pada Remaja - Yashinta, Yashinta; Hurriyati, Dwi (Direktorat Riset dan Pengabdian Masyarakat Universitas Bina Darma Palembang, 2020)
This study aims to determine the relationship of loneliness with problematic internet use on boarding students on Silaberanti street in Siantan jaya Opposite Ulu 1 Palembang city. Research subjects numbered 220 people using random sampling methods. Data was collected using a 60 item problematic internet use scale and a 60 item loneliness. Realibility is generated on scale of problematic internet use of 0,955 and loneliness of 0,946.Hypothesis testing uses product moment correlation analysis techniques. Hypothesis test results showed a positive relationshif between loneliness with problematic internet use on boarding students on Silaberanti street in Siantan jaya Opposite Ulu 1 Palembang city r= 0,684 with a significance level of 0,000 (p<0,01). Loneliness in this study made an effective contribution of 46,8% to problematic internet use which can be seen from the coefficient of determination (rÂ²) that is equel to 0,468.